Exclusion and inequity: a national analysis of disability-inclusive admission criteria in Saudi medical schools - Sayed, Anwar A. (Frontiers in Medicine, 2025)
IntroductionEquitable access to medical education is essential for building a diverse and inclusive healthcare workforce. Despite national disability legislation in Saudi Arabia, the extent to which undergraduate medical programs implement inclusive admission criteria remains unclear. This study evaluates the inclusiveness of admission policies for students with disabilities across all undergraduate MBBS programs in Saudi Arabia.MethodsA cross-sectional review of the official admission policies of 32 universities was conducted. Data were extracted from university websites to identify whether institutions provided inclusive pathways, accommodations for disability, or used exclusionary language or environmental/institutional barriers related to disability.ResultsOnly 6 of 32 universities–exclusively public institutions–had formal disability-inclusive policies. The remaining schools either lacked inclusive provisions, support structures or required medical fitness documentation that could exclude applicants with physical, sensory, or mental impairments. Private universities showed no evidence of inclusive admissions.DiscussionMost Saudi medical schools maintain exclusionary, ambiguous, or unsupportive admission practices, undermining national commitments to disability rights and global Sustainable Development Goals (SDGs 4 and 10). Urgent institutional reforms are needed to dismantle barriers and ensure transparency, equity, supportive environments, and accessibility for applicants with disabilities in health professions education.